Study on health risk assessment due to emissions from diesel power plant using AERMOD modeling / Ibrahim Afrah - Ibrahim , Afrah (2022)
Diesel engines are the most efficient and reliable power plant among all internal combustion engines. While the diesel engine offers an efficient and reliable power source which brings a lot of benefits to the power industry it also contributes harmful emissions to air pollution. In this research, the studied diesel power plant for electricity generation is located in the capital city of Maldives which is among the highest densely populated city to land ratio. Due to the lack of land available in Male’ City the power plant cannot be relocated away from the residential area hence the emissions from the diesel power plant are exposed to the population and the environment. This study aims to identify the pollutants contained in the diesel stack emissions and its concentrations levels. Also, to analyze the predicted short-term and long-term ground concentrations levels. Finally, to conduct a health risk assessment (HRA) and identify short-term and long-term health risk effects. In this study, five pollutants (CO, SO2, NO2, PM10 and PM2.5) were assessed for health risk assessment. The stack emission concentration levels of the pollutant were measured using portable flue gas analyzer and particulate matter analyzer. The results obtained were compared with Malaysian Environmental Quality (Clean Air) Regulations 2014. All the pollutant concentration levels were found to be below the mentioned limit in the guideline. Predicted ground concentration levels were calculated within 3 x 3 km domain of the point source by utilizing AERMOD dispersion model simulation for short-term and long-term dispersion. The results show that for pollutants CO, SO2, NO2, PM10 and PM2.5 the short-term concentrations are 29.91, 59.84, 16.93, 6.05, 4.76 (μg/m3 ) and for long-term 19.99, 2.11, 0.60, 0.65, 0.51 (μg/m3 ) respectively. All the values were compared with Malaysian Ambient Air Quality guidelines and was found be below the critical values. In addition, risk characterization was conducted by utilizing Hazard Quotient (HQ). For all the pollutants, HQ value obtained for short-term and long-term dispersions was less than 1 (HQ<1) hence predicted pollutant concentration levels are below RfC value and considered safe with no potential to cause adverse health effects. Although the study calculated pollutant concentration levels are in acceptable range, the accuracy of the outcome highly depends on the stack emission reading and meteorological data.